The Daily Spiritual Experiences Scale and Well-Being: Demographic Comparisons and Scale Validation with Older Jewish Adults and a Diverse Internet Sample - Kalkstein, Solomon (Journal of religion and health, 2009)
A substantive literature connects spirituality to positive physical, social, and mental health. In this study, the Daily Spiritual Experiences Scale (DSES) was administered to 410 subjects who participated in a community study and to 87 residents at the Hebrew Home for the Aged at Riverdale (HHAR), the latter sample consisting primarily of older Jewish respondents. Internal consistency of the DSES in both samples was high and exploratory factor analyses revealed one dominant factor and a second factor, which included 14 and 2 items, respectively, consistent with the scale's original validation (Underwood and Teresi 2002). Demographic subgroup comparison among religious groups revealed significantly fewer daily spiritual experiences among Jews, and lowest scores among those respondents endorsing no religious affiliation. Women exhibited more frequent daily experience than men, and attainment of higher levels of education was associated with less frequent daily spiritual experience. All but one of the outcome measures of physical and psychologic well-being were found to be positively associated with the DSES so that more frequent daily spiritual experience correlated with less psychopathology, more close friendships, and better self-rated health. Directions for future research, study interpretation and limitations, and clinical implications for use of the DSES are discussed.